Loading of a single implant in simulated bone - Pimduen Rungsiyakull (2018)
This study investigated the effect of occlusal design on the strain developed in simulated bone of implant-supported single crown models. Triaxial strain gauges were attached at the cervical area of each model. Occlusal design, load location, and magnitude were examined to determine the maximum axial principal strains (µε) of four occlusal designs: 30-degree cusp inclination with 4- and 6-mm occlusal table dimensions and a 10-degree cusp inclination with 4- and 6-mm occlusal table dimensions. Statistical differences were found for peak average maximum principal strains between each occlusal design when the applied load was directed along the central fossa and 2 mm buccal to the central fossa along the inclined plane, with strain gauges attached at the cervicobuccal (P < .001) and cervicolingual (P ≤ .001) aspects. In all loading conditions, the 30-degree cusp inclination and 6-mm occlusal table dimension consistently presented the largest strains compared with the other occlusal designs. A reduced cusp inclination and occlusal table dimension effectively reduced experimental bone strain on implantsupported single crowns. The occlusal table dimension appeared to have a relatively more important role than cusp inclination. © 2011 by Quintessence Publishing Co Inc.